Impact of fifteen days fishing ban in the major spawning grounds of hilsa (Tenualosa ilisha Hamilton 1822) on its spawning success (Research in Agriculture Livestock and Fisheries, 2015)
The present study was conducted to assess the impact of fifteen days fishing ban on breeding success of hilsa shad in the major spawning grounds of hilsa in the month of September and October, 2015. The study showed that fishing ban during spawning seasons have significant role in the successful reproduction of hilsa. In and around the spawning grounds among all the captured hilsa, male: female ratio was found 1: 1.86 and percent composition was 35% and 65% respectively. In 2015, percent composition of spent hilsa during major breeding period in the spawning grounds was found 36.60%. The eggs production of hilsa was calculated, in the year 2010, 2011, 2012, 2013, 2014 and 2015 about 336199Kg, 385500Kg, 380400Kg, 447100Kg, 417765Kg and 494365Kg respectively, hilsa eggs could have been produced indicating a positive impact of 15 days fishing ban in the spawning season. Comparatively higher percentages of gravid hilsa were found which were not available in the similar quantity and condition in the fishing ban period in other than spawning areas of hilsa. During the present investigation, fairly higher amount of spent hilsa and juveniles were observed in the spawning grounds. On the other hand, fewer juveniles and spent hilsa were observed in the adjacent areas of the spawning grounds indicating that in comparison to the recent reports there might have little or no changes of the spawning grounds of hilsa occurred. Along with the jatka fry, spawn and fries of other fishes were also found in higher quantity than the previous years and thus it is assumed that 15 days fishing ban also might have positive impact on the successful breeding of other fishes. Overall, the fishing ban was found effective for successful breeding of hilsa.Res. Agric., Livest. Fish.2(3): 491-497, December 2015